2021
DOI: 10.2147/ijgm.s339378
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neutrophil-Lymphocyte Ratio and All-Cause Mortality and Cause-Specific Mortality in US Adults, 1999–2014

Abstract: Background Neutrophil-lymphocyte ratio (NLR) is a novel marker of inflammation. Emerging studies have evaluated the relationship of NLR with cardiovascular diseases and malignant conditions. However, rare studies regarded the association between NLR and long-term health status. This study aimed to evaluate the association of NLR with all-cause mortality and cause-specific mortality among adults in the United States. Methods We obtained eight cycles data of National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This is consistent with a recent cell count study in type 2 diabetes [118] and a study demonstrating an increased neutrophil-to-lymphocyte ratio (NLR) in COPD [119]. An increased NLR has also been recently associated with an increased all-cause mortality [120], with HRs similar to those reported here. Considering individual health outcomes was important: for instance, while the memory B-cell fraction did not correlate with all-cause mortality, an increase in this fraction was associated with an increased risk of cancer and simultaneously with a reduced risk of T2D.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a recent cell count study in type 2 diabetes [118] and a study demonstrating an increased neutrophil-to-lymphocyte ratio (NLR) in COPD [119]. An increased NLR has also been recently associated with an increased all-cause mortality [120], with HRs similar to those reported here. Considering individual health outcomes was important: for instance, while the memory B-cell fraction did not correlate with all-cause mortality, an increase in this fraction was associated with an increased risk of cancer and simultaneously with a reduced risk of T2D.…”
Section: Discussionsupporting
confidence: 92%
“…Second, we have included all clinical stages of melanoma, and there was a balanced proportion between stages. Third, we used MSS as the primary endpoint instead of OS because an elevated NLR is associated with increased all-cause mortality in the general population ( 40 ). Lastly, the cut-off values for NLR, PLR and MLR in our study were determined by using maximally selected rank statistics, which is believed to be a more appropriate method than ROC analysis, which was used in the majority of previous studies ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NLR is increasingly being used as a biomarker for managing various inflammation-associated diseases, such as CVD, cancer, and autoimmune diseases [33][34][35][36]. Kim et al [37] and Sunbul et al [21] have shown that the NLR can be used to predict OSA and its severity.…”
Section: Discussionmentioning
confidence: 99%